Comparative assessment of clinical-paraclinical manifestations of rotavirus infection versus genotypical variety in infants - DONOS, Ala; ALSALIEM, Tatiana; SPINU, Constantin; REVENCO, Ninel; TUREA, Valentin; MIHU, Ion; COJOCARU, Radu; GHEORGHITA, Stela; SPINU, Igor; ILIEV, Albina-Mihaela; SUVEICA, Luminita (One Health & Risk Management, 2021)
Introduction. RVI (rotavirus infection) is the most common cause of dehydration in infants and young children. The implementation of the sentinel surveillance of RVI in infants from 2008 in the Republic of Moldova demonstrated the high rate of this infection (40.0%), being an argument in recommending the antirotaviral immunization in children within the National Immunization Program.Material and methods. The study enrolled 193 children with acute diarrheal disease, included in the sentinel supervision (2012-2016) and treated in the Unit for Acute Diarrheal Diseases at Children’s Clinical Hospital no. 1. The biological material was examined by serological enzyme-linked immunosorbent assay (ELISA) and genotyping, revealed by polymerase chain reaction (PCR). Results. The rotavirus infection was confirmed in 193 infants, of which 121 children were not vaccinated against RVI, and 72 were immunized. Depending on the genotypes encountered before and after vaccination, it was found that G9P [8], G3P[8], G4P[8] were detected before vaccination, although postvaccine prevailed G2P[4], G4P[8]. In addition, the incidence of RVI is decreasing and the disease evolution is much better.Conclusions. This article reflects the evolution of the genotypic properties of rotaviruses and the clinical-paraclinical particularities of RVI in infants, highlighting the importance of the implementation of antiretroviral immunization in children within the National Immunization Program in the Republic of Moldova.